Gremlins don't chew bubble gum - Dadey, Debbie; Jones, Marcia (Marcia Thornton); Gurney, John (New York : Scholastic, 1995)
The Bailey School kids want to find out if Miss Kidwell, the substitute school secretary, is really a gremlin messing up the electricity.
"A little apple paperback."
4.4
3-6
Keywords: Schools -- Fiction; School stories